1982
DOI: 10.1037/0735-7028.13.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Self-help groups: A referral resource for professional therapists.

Abstract: Although self-help groups are not a new phenomenon, only recently has self-help become a topic of significant interest and research. With over a reported one-half million formalized groups, self-help can potentially be a powerful therapeutic resource. This article discusses the nature and structure of self-help organizations, their limitations, and their potential. The effective utilization of self-help organizations requires the referring therapist to become aware of the goals, methods, and services provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Perhaps most important, referral guidelines and suggestions regarding the ways counselors and others can view and use self-help groups as a positive resource in their work are being published in the literature (Rodolfa & Hungerford, 1982;Wilson, 1983). Also, reports are surfacing of successful long-term relationships being established between mental health professionals and self-help groups (Chutis, 1983).…”
Section: The Professions Andmentioning
confidence: 95%
See 1 more Smart Citation
“…Perhaps most important, referral guidelines and suggestions regarding the ways counselors and others can view and use self-help groups as a positive resource in their work are being published in the literature (Rodolfa & Hungerford, 1982;Wilson, 1983). Also, reports are surfacing of successful long-term relationships being established between mental health professionals and self-help groups (Chutis, 1983).…”
Section: The Professions Andmentioning
confidence: 95%
“…The recent literature now reflects not only a receding ambivalence but a strong trend toward symbiotic cohabitation. Of course, the cautions inherent in self-help are still readily defined Rodolfa & Hungerford, 1982;Marmor, 1980). The fostering of overdependency, lack of skills in group dynamics, and the neglect of mental health care through sole reliance on the group have been some of the pitfalls cited.…”
Section: The Professions Andmentioning
confidence: 98%
“…Not necessarily. When the pyramid model is inappropriate, the professional can still treat the autonomous self-help organizations as suitable referral programs (Rodolfa & Hungerford, 1982). Although unable to direct or train members of such groups, a professional can evaluate the groups and refer clients to the most supportive.…”
Section: The Referral Modelmentioning
confidence: 99%
“…Traditional theories aimed at understanding and treating grief related problems (Bowlby, 1963;Freud, 1958;Parkes, 1972) have emphasized intrapersonal factors. Recently, Melges and DeMaso (1980), Worden (1982), and Rodolfa and Hungerford (1982) noted the importance of social systems in recovery from grief. Gorer (1965) suggested that successful psychotherapy with those suffering from MGR must consist of three stages: PROFESSIONAL PSYCHOLOGY: RESEARCH AND PRACTICE 835 This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Social Systems Theory and Mgrmentioning
confidence: 99%